Milk Fat Globule Membrane Supplementation in Formula-fed Rat Pups Improves Reflex Development and May Alter Brain Lipid Composition. Issue 1 (December 2018) - Moukarzel, Sara; Dyer, Roger; Garcia, Cyrielle; Wiedeman, Alejandra; Boyce, Guilaine; Weinberg, Joanne; Keller, Bernd; Elango, Rajavel; Innis, Sheila
Abstract Human milk contains nutritional, immunoprotective and developmental components that support optimal infant growth and development. The milk fat globule membrane (MFGM) is one unique component, comprised of a tri-layer of polar lipids, glycolipids, and proteins, that may be important for brain development. MFGM is not present in most infant formulas. We tested the effects of bovine MFGM supplementation on reflex development and on brain lipid and metabolite composition in rats using the "pup in a cup" model. From postnatal d5 to d18, rats received either formula supplemented with MFGM or a standard formula without MFGM; a group of mother-reared animals was used as reference/control condition. Body and brain weights did not differ between groups. MFGM supplementation reduced the gap in maturation age between mother-reared and standard formula-fed groups for the ear and eyelid twitch, negative geotaxis and cliff avoidance reflexes. Statistically significant differences in brain phospholipid and metabolite composition were found at d13 and/or d18 between mother-reared and standard formula-fed groups, including a higher phosphatidylcholine:phosphatidylethanolamine ratio, and higher phosphatidylserine, glycerol-3 phosphate, and glutamine in mother-reared compared to formula-fed pups. Adding MFGM to formula narrowed these differences. Our study demonstrates that addition of bovine MFGM to formula promotes reflex development and alters brain phospholipid and metabolite composition. Changes in brain lipid metabolism and their potential functional implications for neurodevelopment need to be further investigated in future studies.